The style of the Regent of Madiun in developing the Indonesian Pesilat Village in Madiun Regency - Dony Adi Saputra (Journal Of Social Science (JoSS), 2023)
Departing from the plurality of silat universities and frequent conflicts between silat universities in the Madiun area. The Regent of Madiun created a new legalized identity, namely Madiun Regency "Kampung Pesilat Indonesia". In order to fulfill the socio-political and economic aspects of community life, this new identity is also expected to be a unifier for Silat universities and the preservation of pencak silat culture. According to the Regent of Madiun, Kampung Pesilat Indonesia is the first step in equalizing perceptions in order to have one goal in the commitment to build Madiun Regency so that elements of division or hostility can be avoided. Pencak Silat culture has become the heritage of the Indonesian nation that has been recognized by the world and it is appropriate to be a joint obligation in maintaining and preserving as the nation's local wisdom. The Regent of Madiun is committed through equalizing the perception of Madiun as an Indonesian Pesilat Village in line with its vision and mission. This study wanted to see how the leadership style of the Regent of Madiun in developing Pesilat Village in Madiun Regency and what factors influenced his leadership. The research method used by researchers is descriptive qualitative. There are four leadership styles carried out by the Regent of Madiun in developing Kampung Pesilat Indonesia, namely Authoritarian, Participative, Delegative and Situational. According to sources, this leadership style was carried out by the Regent in developing the martial arts village, both in terms of planning and development.